Active integrated antenna with image reject mixer - Chong, Wah Kiat (2006)
Active integrated antenna (AIA) with image reject mixer (IRM ) operating at licenseless frequency of 2.4 GHz and intermediate frequency (IF) of 50 MHz is proposed. The opted IF of 50 MHz proves to yield satisfactory result in previous rather similar work. In this work, IRM is integrated with microstrip patch antenna on the similar substrate to attain size, weight and cost reduction. The suitable substrate that serves as the common platform for all integral components is FR-4 with dielectric constant of 4.7 and thickness of 1.6mm. This AIA with IRM employs at different phase manipulation approach from that of the previous research in which the RF signal from the antenna feed is initially fed to an 1800 rat race coupler instead of a 900 coupler. Practically, this system is able to achieve image suppression with an isolation of approximately 20 dB between the image and desired frequency with 7 dBm LO drive at 2.35 GHz. The method of moment (MoM) and lumped circuit element simulation using Agilent’s ADS software are employed in this work. The integral components of AIA with IRM consist of microstrip 2-elements patch antenna, singly balanced schottky diode mixers, low pass filter, branchline 900 hybrid coupler lumped element 900 coupler and 1800 rat race coupler. The purpose and significance of this research emerge from the disadvantages that superheterodyne receiver presents in achieving image suppression. Relatively, IRM can reasonably suppress image at a lower size, weight, complexity and cost by means of phase cancellation. The design of AIA with IRM requires the achievement of balance between several inevitable design trade-offs involved. Generally, the trade-offs in this design are between size, simplicity and performance